Strategic marketing for commercial management in online stores - González Marín, Ángel (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2024)
In an increasingly digitized world, strategic marketing for commercial management in online stores has become essential for business success. From optimizing user experience to implementing branding and positioning strategies, these practices are crucial for standing out in a highly competitive market. With the exponential growth of global e-commerce, the adoption of strategic marketing approaches becomes an imperative necessity to reach and retain customers in the vast online world. However, the growing competition in the online space presents challenges such as identifying and retaining customers in a saturated market, optimizing user experience to increase conversions, and effectively managing the brand in an environment where interactions are predominantly virtual. Therefore, the objective was to analyze strategic marketing for commercial management in online stores. Methodologically, three aspects were followed, covering environmental elements, segmentation, as well as tactical or operational business strategies, being documentary in nature, with bibliographic design that served for the compilation of the state of the art on Commercial management in online stores has become increasingly crucial in today's business landscape, where competition is intense and customer attention is a prized asset. In this context, strategic marketing plays a fundamental role; however, a comprehensive understanding of the most effective strategies in this area is essential for success. The general objective was to thoroughly review existing literature on strategic marketing in the context of online stores, in order to identify the most effective strategies for commercial management in this digital environment. Regarding the methodology framed within a qualitative paradigm, the type was documentary, with a bibliographic design and hermeneutic method. Among the relevant results, it was possible to identify several strategic marketing strategies that have proven to be effective for commercial management in online stores. These strategies include personalization of the customer experience, the use of data analysis tools for decision-making, optimization of the e-commerce platform to improve usability and visibility in search engines, and the integration of social networks into the marketing strategy to increase interaction with customers. The importance of strategic marketing in the commercial management of online stores is concluded, emphasizing the need to adopt innovative and adaptive approaches to maintain competitiveness in this constantly evolving digital environment, which requires promoting the effective implementation of strategic marketing strategies to significantly improve the visibility, engagement, and sales of an online store, resulting in sustained growth and a competitive advantage in the digital market.
Keywords: Strategic marketing; Commercial management; Online stores